2013
DOI: 10.1152/jn.00464.2012
|View full text |Cite
|
Sign up to set email alerts
|

Novelty is not enough: laser-evoked potentials are determined by stimulus saliency, not absolute novelty

Abstract: related potentials (ERPs) elicited by transient nociceptive stimuli in humans are largely sensitive to bottom-up novelty induced, for example, by changes in stimulus attributes (e.g., modality or spatial location) within a stream of repeated stimuli. Here we aimed 1) to test the contribution of a selective change of the intensity of a repeated stimulus in determining the magnitude of nociceptive ERPs, and 2) to dissect the effect of this change of intensity in terms of "novelty" and "saliency" (an increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 33 publications
6
115
0
2
Order By: Relevance
“…Other authors have described similar ideas in the literature of Stop Tasks with reward contingencies, using other terms such as the “Arousal Effect” (Shanahan et al, 2008) or the “Novelty effect” (Ronga et al, 2013). The concepts are not equivalent since the effects where not alike.…”
Section: Discussionmentioning
confidence: 83%
“…Other authors have described similar ideas in the literature of Stop Tasks with reward contingencies, using other terms such as the “Arousal Effect” (Shanahan et al, 2008) or the “Novelty effect” (Ronga et al, 2013). The concepts are not equivalent since the effects where not alike.…”
Section: Discussionmentioning
confidence: 83%
“…The EEG data of each block were segmented into 24 epochs using a time window ranging from 0.5 s before to 1.5 s after the laser trigger (total epoch duration: 2 s). Since frequency filtering and ICA might have changed the EEG signals, a second baseline correction was performed using the same −500 to 0 ms reference interval, thus ensuring that the average signal in the pre-stimulus interval was equal to 0 (Valentini et al, 2011;Ronga et al, 2013;Torta et al, 2012). The baseline correction was done by subtracting the mean of the signal of the pre-stimulus.…”
Section: Pre-processingmentioning
confidence: 99%
“…In particular, placebo responses have been found to be associated to a reduction of the amplitude of the biphasic N2-P2 vertex component. Although the functional significance of LEP remains to be fully understood Valentini et al, 2011;Legrain et al, 2012;Torta et al, 2012;Ronga et al, 2013), LEP are often considered the best tool for investigating the nociceptive system (Cruccu and García-Larrea, 2004) for their Figure 5 N2-P2 laser-evoked potentials (LEP) amplitudes. Likewise, Watson et al (2007) found that the decrease in LEP amplitude was related to both the N2 and P2 components.…”
Section: Figurementioning
confidence: 99%
“…Studies show that novelty (Legrain et al, 2003;Legrain et al, 2009;Valentini et al, 2011) and salience (Ronga et al, 2013) of nociceptive stimulation are major determinants of the magnitude of nociceptive event-related potentials. However, these responses can also reflect top-down attentional and emotional modulations acting on the contextual relevance of the nociceptive representation, and associated with the meaning attached to the sensory event (e.g.…”
Section: Discussionmentioning
confidence: 99%